Fiber bragg grating (FBG) optical fiber sensor array for multiplexed temperature measurement [electronic resource] - Nor Adibah Ibrahim, 1988- , author (2011)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Telekomunikasi)) - Universiti Teknologi Malaysia, 2011